Tanshinol inhibits trophoblast cell migration and invasion by regulating Gadd45a in preeclampsia - Yanlin Yang; Haixia Shang; Jingfen Sun; Xiaofeng Shi; Bohui Zhou (Taylor & Francis Group, 2023)
AbstractObjective Tanshinol is an active constituent of Salvia miltiorrhiza that possesses anti-inflammatory, antioxidant, and antibacterial activities. Therefore, this study attempted to detect whether it has a role in the treatment of preeclampsia (PE).Methods In this study, we explored the effect of tanshinol on the development of PE at the cellular level. The effect of tanshinol on cell proliferation was measured by colony formation and EdU assays. The migration, invasion, and in vitro angiogenesis of HTR-8/SVneo cells were detected by wound-healing, transwell, and tube formation assays, respectively. In addition, a PE cell model was established by overexpression of Gadd45a, and this cell model was assessed with the optimal concentration of tanshinol.Results The results show that tanshinol enhanced proliferation, migration, invasion, and tube formation of HTR-8/SVneo cells in vitro. Furthermore, the reduction in proliferation, migration, invasion, and tube formation of cells by Gadd45a overexpression was partially reversed by tanshinol treatment. Tanshinol also inhibited the apoptosis of HTR-8/SVneo cells transfected with Gadd45a.Conclusions In summary, tanshinol promoted proliferation, migration, invasion, and tube formation and inhibited the apoptosis of HTR-8/SVneo cells. It may be a novel therapeutic compound to attenuate the development of PE.